Proposed training program within Bayer's strategy for participants in the ceramic art learning course for the Student Activities Department at the University of Baghdad (المجلة الدولية للعلوم التربوية والآداب, 2025)
Our current research is a proposed training program in light of the Bayer strategy for participants in the ceramic art learning course of the Student Activities Department at the University of Baghdad, covering three semesters. Due to the importance of the topic, the problem was formulated with the following question: (Does the proposed training program in light of the Bayer strategy enhance and develop the skills of trainees in ceramic education courses in the Student Activities Department at the University of Baghdad?  Importance: This research is considered beneficial for both trainers and trainees in the following way: designing such training programs can help trainees develop their skill sets and reduce the time and effort needed to eliminate random performance. Additionally, applying the program in light of the Bayer educational strategy provides trainers with a stable and consistent system to overcome the issue of skill performance. These training programs also benefit training centers by teaching trainers how to create a well-thought-out plan for educating trainees.Objectives: The current study aims to reveal a program based on the Bayer strategy to develop the skills of ceramic course trainees. It also addresses a second objective, which is to design an educational program based on the Bayer strategy and its applicability to participants in the ceramic training course within the temporal and spatial limits of the research. The spatial limit is the pottery hall at the University of Baghdad (Student Activities Department), and the temporal limit is the time of the courses held to teach ceramic shaping skills during the academic year according to the university schedule.Methodology: This research addresses the first chapter and its main titles, defining useful terms for the study, which are the training program and the Bayer strategy, as well as defining ceramics. The second chapter is the core of the current research, which is divided into main titles: training programs and their importance for learners, the concept of strategy and its types in education. The researcher presented the Bayer strategy and its significance in training programs, and the last topic discussed in the second chapter is the art of ceramics and types of shaping methods. In the third chapter, the researcher relied on the case study method when addressing the short time allowed for conducting the training course.Results: The researcher reached a set of results, indicating that it is possible to implement a proposed training program to teach the skill of ceramics art for trainees (affiliated with the University of Baghdad). The program can enhance the efficiency of course trainers and can also develop the artistic ability of trainees in ceramic shaping. The proposed program, based on the Bayer strategy, can mitigate the challenges of the short duration of the course by eliminating randomness in performance